2012
DOI: 10.1111/j.2042-7158.2012.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of liposomes, transfersomes, ethosomes and cubosomes for transcutaneous immunisation: characterisation and in vitro skin penetration

Abstract: We conclude from the in-vitro studies that cubosomes and ethosomes are promising lipid carriers for transcutaneous immunisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 44 publications
(67 reference statements)
1
62
0
3
Order By: Relevance
“…This enables the lipid carriers to fuse with the lipid bilayers of the skin or corneal epithelial cells. From the study of transcutaneous drug delivery, cubosomes showed superior skin retention than liposomes [25]. Therefore, cubosomes are outstanding candidates for the ocular drug delivery system according to their physicochemical features.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the lipid carriers to fuse with the lipid bilayers of the skin or corneal epithelial cells. From the study of transcutaneous drug delivery, cubosomes showed superior skin retention than liposomes [25]. Therefore, cubosomes are outstanding candidates for the ocular drug delivery system according to their physicochemical features.…”
Section: Introductionmentioning
confidence: 99%
“…Transfersomes were prepared by modified thin film hydration method followed by high-pressure homogenization technique (Rattanapak et al, 2012). SPC, EGCG and SC were dissolved in the mixture of chloroform:methanol (4:1 v/v) in a round bottomed flask.…”
Section: Preparation and Optimization Of Transfersomesmentioning
confidence: 99%
“…It has been reported that cubosomes increase permeation of peptides into skin and nasal mucosa by providing increasingly close contact of the peptides to the cells and producing a stronger penetration with rapid extracellular transport. 15,41 On the other hand, cubosomes might facilitate direct transport of NGF into the outer epithelial cells of RWM. Recent literature suggests that transcellular 42 and paracellular 43 pathways for nanoparticles across the RWM may occur.…”
mentioning
confidence: 99%